MAGNETIC RESONANCE TOMOGRAPHY IN DIAGNOSTICS OF OSTEOGENIC SARCOMA IN TEENAGERS - N.V. Gunicheva; T.A. Akhadov; V.N. Shubkin; L.B. Puzhitsky; R.A. Keshishyan ("Paediatrician" Publishers LLC, 2008)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2008; 7(2):146-147)